Seasonal changes in digestive enzyme (trypsin) activity of the copepods Pseudocalanus minutus (Calanoida) and Oithona similis (Cyclopoida) in the Arctic Kongsfjorden (Svalbard) - Lischka, Silke; Gimenez, Luis; Hagen, Wilhelm; Ueberschär, Bernd (Polar Biology, 2007)
Seasonal activities of the digestive enzyme trypsin were measured between August 1998 and May 1999 to study different nutritional strategies of the two copepods Pseudocalanus minutus and Oithona similis in the Arctic Kongsfjorden (Svalbard) using a highly sensitive fluorescence technique. Stage-, depth- and season-specific characteristics of digestive activity were reflected in the trypsin activity. P. minutus females and stage V copepodids (C) had highest trypsin activities in spring during reproduction (197.5 and 145.7 nmol min−1 ng C−1, respectively). In summer stages CIII–V and in autumn stages CIV and V had high activities (80–116 nmol min−1 ng C−1) in the shallow layer (< 100 m) presumably as a consequence of prolonged feeding before descending to overwintering depth. Trypsin activities at depth (> 100 m) in summer and autumn were low in stages CIII and CIV (29–60 nmol min−1 ng C−1) and in winter in all stages in both layers (20–43 nmol min−1 ng C−1). Based on low trypsin activity, males most likely did not feed. In O. similis, the spring phytoplankton bloom did not significantly affect trypsin activity as compared to the other seasons. O. similis CV and females had high trypsin activities in summer in the deep stratum (304.5 nmol min−1 ng C−1), which was concomitant with reproductive processes and energy storage for overwintering. In autumn, stage CV and female O. similis had significantly higher activities than stage CIV (130–152 versus 78 nmol min−1 ng C−1), which is in accordance with still ongoing developmental and reproductive processes in CVs and females. Comparisons of both species revealed different depth-related responses emphasizing different nutritional preferences: the mainly herbivorous P. minutus is more actively feeding in the shallow layer, where primary production occurs, whereas the omnivorous O. similis is not as much restricted to a certain depth layer, when searching for food. P. minutus had lower levels of trypsin activity during all seasons. In contrast to P. minutus, higher ...